Public Relations Marketing Program of Regional General Hospital (RSUD) in Bandung Regency in Building Communication with the Public - Renata Anisa; Retasari Dewi; Yustikasari Yustikasari (International Journal of Economics and Management Research, 2025)
The development of technology and information accompanied by the growth of the number of hospitals has encouraged the hospital business to become increasingly competitive. Currently, government and private hospitals implement various marketing public relations strategies to build trust, increase loyalty, and build company reputation. The purpose of this study is to describe the marketing public relations program of regional general hospitals in Bandung Regency in building communication with the public. This study uses a qualitative approach with descriptive studies. The data collection techniques used were literature studies, observations, and in-depth interviews. The results of the study show that hospitals implement marketing public relations to build communication with the public. The marketing public relations program implemented by the hospital is health promotion, patient services, special events, and collaboration with external publics. Health promotion is carried out to improve the level of public health. Patient services are provided to serve various queries and consultations from patients. Special events are held in collaboration with third parties such as foundations, communities, and companies. Meanwhile, collaboration is carried out with insurance, companies, and mass media. Digital media and mass media are used to optimize health education to the wider community.